Decline in alcohol use among adolescents in Slovakia: a reason for optimism? - Baška, T; Madarasová-Gecková, A; Bašková, M; Krajčovič, A (Public health, 2016)
OBJECTIVES: To analyze selected indicators of alcohol use (lifetime use, initiation of drinking at ≤13 years of age, weekly use, beverage preferences, initiation of drunkenness at ≤13 years of age and lifetime drunkenness) in adolescents in Slovakia from 2006 to 2014. STUDY DESIGN: The Health Behaviour in School Aged Children (HBSC) study is a cross-sectional questionnaire study. METHODS: A standardized uniform questionnaire was used in representative samples of 11-, 13- and 15-year-old adolescents. In Slovakia, the HBSC study was undertaken in 2006 (n = 3972), 2010 (n = 5089) and 2014 (n = 4369). RESULTS: Over the study period, decreases were observed in weekly drinking (from 34.3% to 21.0% in 15-year-old boys and from 22.1% to 11.9% in 15-year-old girls), lifetime drinking and initiation of drinking at ≤13 years of age. In terms of beverage preferences, the reduction in beer consumption was most notable. Approximately one-third of respondents got drunk for the first time at ≤13 years of age, and this remained consistent throughout the study period. CONCLUSIONS: The declining trend in alcohol use among adolescents in Slovakia may reflect a progressive change in the social environment and is attributable, at least in part, to policy improvements such as pricing and stricter legislation and enforcement.
Keywords: Public Policy; Cross-Sectional Studies; Adolescents; mladiství; Alcoholic Intoxication; průzkumy a dotazníky; mužské pohlaví; otrava alkoholem; průřezové studie; alkoholické nápoje; dítě; Child; Alcoholic Beverages; Slovakia; chování spotřebitelů; Consumer Behavior; Slovenská republika; ženské pohlaví; Humans; Policy; Surveys and Questionnaires; veřejná politika; Alcohol drinking; Alcohol Drinking; pití alkoholu; Female; Adolescent; Epidemiology; lidé; Male